2014
DOI: 10.1016/j.bjid.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Congenital toxoplasmosis in a reference center of Paraná, Southern Brazil

Abstract: This study describes the characteristics of 31 children with congenital toxoplasmosis children admitted to the University Hospital of Londrina, Southern Brazil, from 2000 to 2010. In total, 23 (85.2%) of the mothers received prenatal care but only four (13.0%) were treated for toxoplasmosis. Birth weight was <2500g in 37.9% of the infants. During the first month of life, physical examination was normal in 34.5%, and for those with clinical signs and symptoms, the main manifestations were hepatomegaly and/or sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 38 publications
1
19
0
16
Order By: Relevance
“…In addition, it should be considered that the evaluated patients were diagnosed in the last gestational trimester and started receiving treatment after 30 weeks of gestation. This fact reaffirms the importance of diagnosis pregnant women through serology is essential for fast and efficient treatment to reduce cases of congenital toxoplasmosis [29,30].…”
Section: Sag1 5'sag2 3'sag2mentioning
confidence: 67%
“…In addition, it should be considered that the evaluated patients were diagnosed in the last gestational trimester and started receiving treatment after 30 weeks of gestation. This fact reaffirms the importance of diagnosis pregnant women through serology is essential for fast and efficient treatment to reduce cases of congenital toxoplasmosis [29,30].…”
Section: Sag1 5'sag2 3'sag2mentioning
confidence: 67%
“…In acute congenital toxoplasmosis, the evaluation of Valid N (listwise) 980 A D C A IgG AVIDITY was first step and then the measurement of biochemical factors such as serum transaminases, serum bilirubin and serum ferritin was important. [26][27][28][29][30][31][32][33] In Iran there are no study about biochemical factors in discrimination of acute and chronic toxoplasmosis but in this study, we found many differences in biochemical factors of acute and chronic toxoplasmosis.…”
Section: Discussionmentioning
confidence: 92%
“…En la toxoplasmosis fetal grave, las imágenes diagnósticas del cráneo se suelen evidenciar ventriculomegalia asociada con múltiples nódulos ecodensos, destrucción del cerebro, disgenesia del cuerpo calloso (38-40) y calcificaciones nodulares (41,42).…”
Section: Figuraunclassified